Drug Resistance and Cardiovascular Safety of Second-Generation Anti-Androgens in Patients with Advanced Prostate Cancer - Shahabi Raberi, Venus; Shariati, Akram; Abbasnezhad, Mohsen; Aslanabadi, Naser; Abbasnezhad, Amirreza; Bahmani, Amir (Galen Medical Journal, 2022)
Prostate cancer is recognized as one of the most common cancers affecting the male population. The prostate is revealed to be a hormone-dependent tissue as testosterone and dihydrotestosterone could bind to the androgen receptor, activate it, and initiate the nuclear translocation of this receptor which is followed by subsequent signaling cascades. Regarding this androgen dependency of the prostate, it is believed that androgen deprivation therapies are able to confront aggressive prostate cancer as first-line treatment. However, prostate cancer could overcome hormone deprivation strategies through a number of cellular mechanisms, such as intratumoral androgen production and the production of ligand-independent androgen receptor splice variants, which are known clinically as castration-resistant prostate cancer. Due to the limited efficacy of first-generation antiandrogens in complete blockage of androgen receptor activity, recently, four second-generation anti-androgens, including abiraterone acetate, enzalutamide, apalutamide, and darolutamide approved by the Food and Drug Administration, and considered standard of care for patients with advanced prostate cancer. Nevertheless, prostate cancer cells may acquire drug-resistance mechanisms to overcome these novel chemotherapeutics. Furthermore, potential adverse effects on nontargeted organs such as the cardiovascular system, are possible. Hence, the current study aimed to review the efficacy and cardio-safety of these novel therapeutical strategies.